Stronger Together : Intra-Household Cooperation and Household Welfare in Malawi - McCarthy, Nancy (World Bank, Washington, DC, 2017)
It has long been recognized that household decision-making may not result in outcomes consistent with the unitary household model. Within the collective bargaining framework, consumption decisions would be driven by the spouse with greater bargaining power, while the outcomes would still be Pareto efficient. Within the non-cooperative framework, households would not achieve Pareto efficient outcomes, and under the simplest representation, bargaining power would not affect consumption decisions. This paper develops a model that allows consumption patterns and labor supply to be affected by both bargaining power and non-cooperation. The model highlights the potential gains from improving bargaining power versus increasing cooperation between spouses, and presents conditions under which relatively large gains would be expected from moving to more equitable bargaining power versus achieving intra-household cooperation. The model's predictions are in turn tested using a unique panel data set on married couples in rural Malawi. The analysis shows that, relative to increasing wives' bargaining power, improving cooperation between spouses would exert larger and statistically significant positive impacts on total household income and consumption expenditures per capita, as well as the share of household consumption devoted to public goods. Supported also by cross-country qualitative research, the results suggest that household public goods are relatively important to both women and men in rural Malawi, husbands' capacity to control wives' incomes is relatively limited, and development programs that promote intra-household cooperation could lead to greater gains in income and household public goods provision compared with interventions focusing exclusively on women's empowerment.